Recurrent injury patterns in adolescent rugby. (September 2018) - Archbold, H.A.P.; Rankin, A.T.; Webb, M.; Nicholas, R.; Eames, N.W.A.; Wilson, R.K.; Henderson, L.A.; Heyes, G.J.; Davies, R.; Bleakley, C.M.
Abstract: Objectives: To establish patterns of subsequent injury in U18 rugby, to quantify the burden of within season injury recurrence. Design: Secondary analysis of prospective data. Setting: 28 Schools in Ireland. Participants: 825 male rugby players (aged 15–18 years). Main outcome measures: Subsequent injuries were classified as: new, local or recurrent (same site and type as index injury). All recurrent injuries were sub-grouped by body part and diagnosis. Burden was based on frequency, days lost and injury proportion ratios. Results: A total of 426 injuries were eligible for analysis, of which, 121 were subsequent injuries. The majority of subsequent injuries involved a different body part than their index injury. There were n = 23 cases of within season recurrence. 78% of recurrences occurred within 2 months of return to play. Recurrent injuries comprised 5% of all injuries and their cumulative time loss was 1073 days. Recurrent injury to the ankle ligaments, lumbar muscles and concussions carried the greatest burden. Conclusion: The burden of recurrent injury in U18 rugby is lower than in the professional game. However, this population could benefit from targeted secondary prevention efforts including reconsideration of return-to-play protocols for ankle sprain, lumbar muscles and potentially concussion. Highlights: Recurrent injuries comprise 5% of all injuries occurring in a single season of adolescent rugby union. On average, there were 0.8 recurrences reported per school per season. Recurrent injury to the ankle ligaments, lumbar muscles and concussions carry the greatest burden. 78% of recurrences were defined as 'early', occurring within 2 months of returning to play. There were trends that recurrent injuries are more severe than index injuries.